Changes in the requirement for early surgery in inflammatory bowel disease in the era of biological agents. Issue 12 (10th May 2020) - Guasch, Montserrat; Cañete, Fiorella; Ordás, Ingrid; Iglesias‐Flores, Eva; Clos, Ariadna; Gisbert, Javier P.; Taxonera, Carlos; Vera, Isabel; Mínguez, Miguel; Guardiola, Jordi; Rivero, Montserrat; Nos, Pilar; et al.
Abstract: Background and Aim: Biological therapies may be changing the natural history of inflammatory bowel diseases (IBDs), reducing the need for surgical intervention. We aimed to assess whether the availability of anti‐TNF agents impacts the need for early surgery in Crohn's disease (CD) and ulcerative colitis (UC). Methods: Retrospective, cohort study of patients diagnosed within a 6‐year period before and after the licensing of anti‐TNFs (1990–1995 and 2007–2012 for CD; 1995–2000 and 2007–2012 for UC) were identified in the ENEIDA Registry. Surgery‐free survival curves were compared between cohorts. Results: A total of 7370 CD patients (2022 in Cohort 1 and 5348 in Cohort 2) and 8069 UC patients (2938 in Cohort 1 and 5131 in Cohort 2) were included. Immunosuppressants were used significantly earlier and more frequently in both CD and UC post‐biological cohorts. The cumulative probability of surgery was lower in CD following anti‐TNF approval (16% and 11%, 22% and 16%, and 29% and 19%, at 1, 3, and 5 years, respectively P < 0.0001), although not in UC (3% and 2%, 4% and 4%, and 6% and 5% at 1, 3, and 5 years, respectively; P = 0.2). Ileal involvement, older age at diagnosis and active smoking in CD, and extensive disease in UC, were independent risk factors for surgery, whereas high‐volume IBD centers (in both CD and UC) and immunosuppressant use (in CD) were protective factors. Conclusions: Anti‐TNF availability was associated with a reduction in early surgery for CD (driven mainly by earlier and more widespread immunosuppressant use) but not in UC.